Chapter The Emissions of the Tagoro Submarine Volcano (Canary Islands, Atlantic Ocean): Effects on the Physical and Chemical Properties of the Seawater - Santana-Casiano, Juana Magdalena (InTechOpen, 2018)
This chapter presents the changes and evolution of the physical and chemical properties of the seawater south of the El Hierro Island (Canary archipelago, Atlantic Ocean) as a consequence of the emissions of the Tagoro submarine volcano, over a 6 year study from 2011 to 2016. Since the eruption, a series of oceanographic studies have been carried out in the area focusing on the evolution of the redox potential and the pH, two master variables that control the chemical equilibrium in sea water. The changes experienced by the carbon dioxide system, the variations in the concentration of Fe(II) and their correlation with the decrease in the pH during the evolution of the volcano, from the beginning of the eruptive stage to the post-eruptive phase, are discussed. The increased TDFe(II) concentrations and the low associated pHT values have controlled the occurrence of an important fertilization event in the sea water around the volcano at the Island of El Hierro, providing optimal conditions for the regeneration of the area. The sites like the Tagoro submarine volcano, in its degasification stage, provide an excellent opportunity to study the carbonate system in a high CO2 world, the volcanic contribution to the global volcanic carbon flux and the potential environmental impact of these emissions on the surrounding ocean and the ecosystem.